Study On Coastal Sediment Properties And Water Quality At Pantai Perpat, Batu Pahat, Johor - Hamid, Nor Baizura; Mokhtar, Mardiha; Daud, Mohd Effendi; Kaamin, Masiri; Abdullah, Noorul Hudai; Mohammad Azmi, Mohamad Azim; Jaharsah, Norhafisah; Hamdan, Muhammad Hazmi (Gae, 2025)
This study was conducted at Pantai Perpat, Batu Pahat, Johor, to investigate the correlation between suspended sediment concentration and particle size distribution. The objectives included identifying water quality parameters, assessing suspended sediment levels, and studying correlations across coastal zones. Water and sediment samples were collected from twelve stations using the grab sampler method, with parameters such as pH, temperature, total suspended solids (TSS), turbidity, sediment size, and moisture content analyzed in designated laboratories. Variability in coastal water quality was observed, with pH values ranging from 7.40 to 7.77 and temperatures from 24.97°C to 26.33°C, indicating acceptable levels. Zone 1 exhibited high turbidity (699 NTU) and TSS concentration (12,393.33 mg/L), suggesting potential issues. Sediment size distribution varied among coastal zones: Zone 1 had a mix of various sediment sizes, primarily silty clay, while Zones 2, 3, and 4 consisted mainly of sandy sediments. Correlations between turbidity and median grain size (D50) varied across the zones, with strong correlations in Zone Middle Tide (MT) (R² = 0.7836) and Zone High Tide (HT) (R² = 0.5846), and a weak correlation in Zone Low Tide (LT) (R² = 0.0124). Strong correlations were also found between TSS and D50 in Zone MT (R² = 0.9924), with moderate and weak correlations in Zones HT (R² = 0.3384) and LT (R² = 0.146), respectively. Understanding water quality and sediment characteristics is crucial for effective environmental management and coastal planning. These findings provide valuable insights for decision-makers involved in coastal development projects. Further research should focus on long-term monitoring and sediment transport dynamics to support sustainable coastal management